Pre Synchronization Control Strategy of Virtual Synchronous Generator (VSG) in Micro-Grid - Jianfeng Wang; Nurulazlina Ramli; Noor Hafizah Abdul Aziz (IEEE Access, 2023)
The constant increase of energy demand and the widespread adoption of renewable energy sources have led to the significant interest in micro-grids, which are small-scale power systems that utilize distributed energy resources. However, micro-grids face synchronization challenges in terms of stability and reliability, and virtual synchronous generator technology has become the key to addressing this issue. This study focuses on the pre synchronization control strategy of virtual synchronous generators in micro-grids, aiming to solve the potential surge current problem that virtual synchronous generators may generate when switching from off grid mode to grid connected mode through innovative methods. This strategy employs a phase difference acquisition method that eliminates the need for a phase-locked loop. It calculates virtual power by utilizing the output voltage of the virtual synchronous generator and the grid side voltage, and obtains the phase difference through calculation. The resulting phase difference is then used as input for the frequency phase synchronization unit in pre-synchronization. By adjusting the diagonal frequency, the phase difference $Δ θ $ can be modified to achieve pre-synchronization before connecting the virtual synchronous generator to the power grid. This method notably reduces the dependence on the phase-locked loop and enhances the stability and reliability of the system. The paper has effectively solved the synchronization problem of virtual synchronous generators in micro-grids through innovative pre synchronization control strategies and improved secondary frequency regulation strategies. It is hoped that these research results will provide new ideas and methods for the further development and application of micro-grid technology.